In vivo 31P MR spectroscopy of human kidney grafts using the 2D-chemical shift imaging method - Vyhnanovská, P; Dezortová, M; Herynek, V; Táborský, P; Viklický, O; Hájek, M (Transplantation proceedings, 2011)
The aim of this work was to evaluate the possibility to use in vivo (31)P magnetic resonance spectroscopy (MRS) for the diagnosis of kidney graft dysfunction after transplantation. We examined 68 kidney grafted patients using a 1.5 T MR scanner. (31)P MRS was performed using the 2D-chemical shift imaging method. The patients were divided into 4 groups: acute rejection episode; acute tubular necrosis; late graft dysfunction; or good renal function. We measured the signal intensities of phosphomonoesters (PME), inorganic phosphate (Pi), phosphodiesters (PDE), and α-, β-, γ-adenosine triphosphate (ATP; with contributions of α- and β-adenosine diphosphate) and their ratios. Patients with an acute rejection episodes showed a significantly elevated PME/β-ATP and PDE/β-ATP, PME/Pi, and PDE/Pi signal ratios compared with the control group. The group with acute tubular necrosis had decreased ratios. Patients with late graft dysfunction revealed only an insignificant decrease in PME/Pi and PDE/Pi ratios. We concluded that (31)P MRS was capable of distinguishing the two main causes of graft dysfunction early after transplantation.
Keywords: transplantace ledvin; Phosphorus Isotopes; dospělí; Kidney; lidé středního věku; magnetická rezonanční spektroskopie; lidé; izotopy fosforu; Female; mužské pohlaví; Magnetic Resonance Spectroscopy; Kidney Transplantation; Male; ledviny; Middle Aged; Adult; ženské pohlaví; Humans